2019
DOI: 10.12669/pjms.35.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcome of Post-Neonatal Tetanus in an intensive care unit of a Tertiary Care Hospital

Abstract: Objective: To determine the prognostic factors and outcome of tetanus in children of post-neonatal age admitted in the intensive care unit (ICU) of a tertiary care hospital. Methods: This prospective cross sectional study, carried out in the Pediatric ICU of The Children’s Hospital Lahore from Jan 2013 to March 2017. Children of both genders with age range of two months to 16 years diagnosed clinically as tetanus were included. All 132 patients were scrutinized for all possible risk factors, need for mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In concordance with other studies, [26,27,33,39] although not statistically significant, the CFR was higher among children with severe and very severe disease and those with short incubation period of less than 7 days. [35] Studies in Pakistan, [40] India [35] and Ethiopia [33] reported that the presence of complications especially autonomic instability in patients with PNT was associated with higher case fatality rates as also observed in this study. Also worrisome is the higher CFR observed in the first 7 days of admission as also seen in other studies in Nigeria [27] and outside the country.…”
Section: Discussionsupporting
confidence: 81%
“…In concordance with other studies, [26,27,33,39] although not statistically significant, the CFR was higher among children with severe and very severe disease and those with short incubation period of less than 7 days. [35] Studies in Pakistan, [40] India [35] and Ethiopia [33] reported that the presence of complications especially autonomic instability in patients with PNT was associated with higher case fatality rates as also observed in this study. Also worrisome is the higher CFR observed in the first 7 days of admission as also seen in other studies in Nigeria [27] and outside the country.…”
Section: Discussionsupporting
confidence: 81%